Tanzania Economic Update, No. 6 : The Elephant in the Room - Unlocking the Potential of the Tourism Industry for Tanzanians - World Bank Group (Washington, DC, 2015)
The focus of this economic update is the tourism sector, which is clearly central to Tanzania s drive toward economic emergence. Riding on the country s bountiful natural assets, tourism is a fast growing sector that is not only providing jobs but is also bringing in much-needed foreign currency. This sector already benefits from substantial attention from the country s leadership, notably in the context of the national business council that recently prioritized tourism as a high growth industry and a major source of job creation. Nevertheless, more can be done to increase benefits so they can be felt more broadly across society. This update proposes three strategic directions towards achieving this goal: (i) the diversification of tourism activities, in multiple dimensions; (ii) further integration in to the sector of stakeholders such as local communities and small operators; and (iii) good governance in the management of fiscal revenues as well as in the use of natural assets. This update also assesses the current state of the Tanzanian economy. While recent developments remain globally positive with high and stable GDP growth and with the inflation rate currently in check, fiscal risks for Tanzania have been growing. During the last fiscal year, the Government missed its revenue targets and was forced to cut priority expenditures and accumulate arrears with contractors and pension funds.